Working towards a new normal: a meta-synthesis of patient-reported aspects of a good life with heart disease - Lisa Nebel; Timothy R. Le Butt; Christoph Herrmann-Lingen; Daniel Broschmann (Health and Quality of Life Outcomes)
Abstract Aims This meta-synthesis challenges the medical notion of health-related quality of life (HRQOL) by identifying aspects of the more holistic philosophical concept of the good life from the perspective of patients with heart disease. Design Systematic meta-synthesis. Methods Following preregistration on PROSPERO, a systematic literature search was conducted in PubMed, PsycInfo, PsycArticles, and PSYNDEX from February 2023 to March 2024. Studies focusing on the experiences of adults living with heart disease were included based on predefined criteria. Articles were assessed for methodological quality using a modified CASP tool, and data synthesis followed Interpretative Phenomenological Analysis. Reporting adheres to PRISMA and ENTREQ guidelines. Results Forty-three articles were included, revealing the overarching theme of “Working towards a new normal,” with four sub-themes: (1) Feeling safe in my own body again, (2) Important relationships provide security and meaning, (3) Taking my life into my own hands again and (4) Living more consciously. Conclusions While HRQOL is a valuable and widely used concept, it primarily captures quality of life from a functional perspective. Qualitative studies on individuals with heart disease reveal the additional aspects of coherence, connectedness, and self-determination that align more closely with the concept of a good life. Implications To enhance care and counseling for patients with heart disease, the concept of HRQOL should be broadened to incorporate preferences, interests, and needs regarding life planning, aligned with the notion of a good life.